Misja i monastycyzm manichejski w dolinie Nilu i jego wpływ na tamtejsze chrześcijaństwo na przełomie III/IV wieku - Scholz, Piotr O. (Vox Patrum, 2015)
Since the discovery of the substantial corpus of Manichaean writings, especially the Kephalaia (editio princeps Polotsky-Böhlig, 1934-1940), the Cologne Mani Codex (= CMC), and the hitherto incompletely published library from Dachla (Ian Gardner, 2000), there can be no doubt as to the activities of the missionaries of the great Persian gnostic Mani in the Southern Nile Valley and Red Sea regions. This fact not only confirms the views of J. Helderman “that the Manichaean missionaries entered Egypt from the South-East, i.e. initially to Upper Egypt” (‘Manichäische Züge im Thomasevangelium’, 483f., note 42), but also the historical observations concerning the origins and development of monasticism. The latter was not without Manichaean influence, not merely in Egypt, but also in Nubia and Ethiopia. A mosaic, seemingly depicting Mani (from the collection of Elie Borowski), testifies to the pictorial needs of the Manichaeans as do the mural paintings from Pachoras/Faras depicting the likeness of Onophrios. These demonstrate the popularity of the crinite ascetic”, a figure also found in the CMC. It is imperative to recall the decisive importance of the southern kingdoms along the Red Sea during the Axial Age (Karl Jaspers), in order to kindle historical awareness in Europe of this currently overlooked region on the eve of its islamicisation – something which for decades I have noted the importance of in numerous publications (cf. foot-note 40). Here, local Christianity (viewed anachronistically) was marked by a heretical-gnostic diversity from the very beginning, which in turn weakened the spread of Christian teaching in the region. Islam was initially seen here by some as a Christian heresy (as pointed out by A. v. Harnack) and which even became accepted (e.g. in Ethiopia or Nubia, as noted by H. Jansen, Muhammed [German ed.: Münich 2008], 141). Thus, the local doctrinal pluriformity of Christianity during the jāhiliyya prepared the way for the later Islamic expansion. Manichaeism belongs unequivocally to the “periphery cultures of the Christian world” (Pogranicza chrześcijaństwa) as well as constituting a part of expanding Christianity in the Late Antique world. Manichaeism still holds many secrets, but at the same time their answers, as illustrated by this article. Hence, the gnostic element of Early Christianity is worthy of continued intensive study, something which unfortunately in Poland is still quite inadequate.